Utilization of local Natural Resources Palm Leaf sticks (Elaeis Guineensis) Based on Local Wisdom Pematang Seleng Village - Ilham Hakiki Harahap; Nurlina Ariani; Amin Harahap; Rury Rimenta imnz Diaz; Tata Suhita Pramesty (International Journal of Community Service Implementation, 2024)
This encoding activity for the community was carried out with the aim of helping residents of Pematang Seleng Village, bar Hulu Hulu District, Labuhanbatu Regency in utilizing palm oil stick waste (Elaeis guineensis) into handicraft innovations that have selling value. Waste products from oil palm sticks (Elaeis guineensis) in the form of fruit containers and other household items such as mirrors. The population in this study is 50 people in Pematang Seleng Village. People in the village are still rarely utilizing palm oil stick waste as the potential of local wisdom to be used into goods with an economical selling price. The use of palm oil sticks as a basic material for making household furniture is one solution to reduce plantation waste while creating economically valuable products. This study aims to describe the process and the potential of oil palm sticks as household furniture materials using qualitative descriptive method. Data were collected through interviews with artisans and field observations, and supported by related literature studies. The results showed that oil palm sticks have good strength and flexibility, and are easily processed into various products such as fruit holders, mirrors and other household furniture. However, the challenges faced include the lack of modern processing techniques and limited market access. With the support of training, technology, and promotion, the utilization of oil palm sticks can be further developed as an environmentally friendly creative industry and has the potential to improve people's welfare.